PENGUJIAN BERAT JENIS DAN PENYUSUTAN BERAT BAHAN UJI KABEL JENIS N2XSRY DAN NA2XSEYBY - -, Syafriyudin (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2012)
Cable channel that serves the electrical energy is the most vulnerable equipment in the installation of security. The occurrence of short circuit in the installation of household is usually caused by bad cable connection or because of damage to cable insulation. To anticipate the damage to cable insulation, required the knowledge of the factors that cause the damage is and how great the influence of these factors on insulation resistance. The effect of temperature can cause the wiring insulation degradation process because it can result in changes in the chemical structure of the material. Degaradasi this process is marked by a decrease insulation resistance, which is characterized by the rapid occurrence of breakdown voltage if the temperature continues to increase. The longer and higher temperature insulation material given the level of damage suffered by the material will also be greater. From the results of testing insulation resistance reduction characteristics can vary from insulating materials d test, depending on the percentage of additive materials are mixed with an insulating material, the degradation process continues over time due to a rise in temperature can cause the wiring insulation becomes stiff and the consequent breakdown voltage to the material will be faster.